2013
DOI: 10.1002/bdrb.21042
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibin B Response to a Motilin Receptor Agonist in Male Rats

Abstract: There was poor correlation between changes in serum levels of Inhibin B and testis histopathology. Based on these observations, the utility of Inhibin B as a hormonal marker for germ cell toxicity is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The large scale of this multi-corporation consortium study was able to confirm inhibin B decreases after sufficient damage, regardless of mechanism or toxicant class (Chapin et al, 2013b;Coulson et al, 2013b;Enright et al, 2013;Erdos et al, 2013;Sonee et al, 2013). However, analytic and interanimal variability will make it difficult to sensitively and reliably detect treatment-related decreases (Breslin et al, 2013;Chapin et al, 2013b;Ziejewski et al, 2013). Decreases in inhibin B were detected when significant testicular lesions were observed; however, decreases were generally not detected with less severe pathology or prior to the development of notable pathology.…”
Section: Figmentioning
confidence: 90%
See 1 more Smart Citation
“…The large scale of this multi-corporation consortium study was able to confirm inhibin B decreases after sufficient damage, regardless of mechanism or toxicant class (Chapin et al, 2013b;Coulson et al, 2013b;Enright et al, 2013;Erdos et al, 2013;Sonee et al, 2013). However, analytic and interanimal variability will make it difficult to sensitively and reliably detect treatment-related decreases (Breslin et al, 2013;Chapin et al, 2013b;Ziejewski et al, 2013). Decreases in inhibin B were detected when significant testicular lesions were observed; however, decreases were generally not detected with less severe pathology or prior to the development of notable pathology.…”
Section: Figmentioning
confidence: 90%
“…Beyond technical performance, the consortium was most interested in the correlation between decreases in circulating inhibin B levels and the development of testicular pathology in the rat; therefore, a series of rat pathogenesis studies were conducted with approximately 20 different compounds (Table 2) covering diverse mechanisms of testicular toxicity across different laboratories (AbbVie, AstraZeneca, Boehringer Ingelheim, Covance, Eli Lilly, GlaxoSmithKline, Janssen, Merck, Pfizer, and Sanofi) and reported in a special issue of Birth Defects Research Part B (98[1], 2013) (Breslin et al, 2013;Chapin and Kim, 2013;Chapin et al, 2013aChapin et al, , 2013bCoulson et al, 2013b;Enright et al, 2013;Erdos et al, 2013;Moffit et al, 2013;Pfaff et al, 2013;Sonee et al, 2013;Stewart et al, 2013;Ziejewski et al, 2013). Exposure scenarios and recovery periods varied between companies to reflect real-world testing strategies.…”
Section: Figmentioning
confidence: 99%
“…And the dogma holds that Inhibin B acts as the feedback partner for Follicle Stimulating Hormone (FSH) (reviewed in Makanji et al, 2011). But this relationship is clearly neither 1:1 nor linear (see Ziejewski et al, 2013, Table 2 and Chapin et al, 2013, Fig. 4) and in some cases, no relationship between Inhibin B and FSH could be found (for humans, Carlsen et al, 1999).…”
Section: Biologymentioning
confidence: 99%
“…We did not determine the specificity of the protein (i.e., that it comes only from the testis). The pathogenesis correlation studies are reported in the nine preceding articles in this issue of Birth Defects Research (Breslin et al, ; Chapin et al, ; Coulson et al, ; Enright et al, ; Erdos et al, ; Moffit et al, ; Pfaff et al, ; Sonee et al, ; Ziejewski et al, ). The present paper is intended to review and discuss the data presented by each of these preceding reports.…”
Section: Introductionmentioning
confidence: 99%